Gouvernance d’entreprise et mobilité/ liquidité du capital : quel ancrage territorial dans une économie financiarisée ? - Corpataux, José; Crevoisier, Olivier (My University, 2011)
L’industrie financière a construit une disjonction fonctionnelle et spatiale entre investisseurs et entrepreneurs, jetant ainsi les bases de ce que l’on appelle aujourd’hui la corporate governance. Cet article propose une approche territoriale de la gouvernance d’entreprise. Il montre dans un premier temps comment le succès de l’industrie financière est dû à la mobilité/liquidité du capital et au court-circuitage des contraintes locales inhérentes à l’économie réelle, notamment dans le domaine du marché du travail et de l’environnement. En second lieu, il décrit les modalités tout à fait particulières dont la corporate governance ancre le capital mobile dans le territoire., The finance industry has created a functional and spatial separation between business investors and entrepreneurs, thereby laying the foundations of what is now referred to as corporate governance. This article presents a territorial understanding of corporate governance. It shows first that the success of financial markets is probably due to the construction of the “mobility liquidity” of capital and to the short-cutting of local constraints of the real economy, notably of labour markets and environmental resources. Second it suggests that corporate governance is the very particular way how mobile capital anchors in firms and regions today.
Corporate governance and the mobility / liquidity ofcapital: what kind of anchoring in a financialised economy?
Keywords: gouvernance d’entreprise; mobilité/liquidité des capitaux; territoire; investisseurs institutionnels; circuits courts; durabilité; territorial governance; mobility/liquidity of capital; territory; institutional investors; short circuits; sustainability